Humanistic Education in Abdurrahman Wahid’s - Supriyanto, Supriyanto (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2018)
Human values are one of the main components of concern in the education field. One of the Muslim scholars who had very high concern for issues related to humanity was Abdurrahman Wahid or who was familiarly called Gus Dur. For Gus Dur, appreciation of human values is at the core of the teachings of Islam. The emphasis on understanding humanity provides a basis for the humanistic attitude that Gus Dur wanted to build. Humanistic education in the concept of Gus Dur is a discussion of human values voiced by Gus Dur which includes universal humanity, human rights and justice. Therefore, this paper intends to discuss humanistic education in Gus Dur’s perspective. Keywords: Nilaihumanistic education, human right, justice, Abdur Abstrak rahman Wahid nilai kemanusiaan adalah salah satu komponen utama yang menjadi perhatian di bidang pendidikan. Salah satu cendekiawan Muslim yang memiliki kepedulian yang sangat tinggi terhadap masalah yang berkaitan dengan kemanusiaan adalah Abdurrahman Wahid atau yang akrab disapa Gus Dur. Bagi Gus Dur, penghargaan terhadap nilainilai kemanusiaan adalah inti dari ajaran Islam. Penekanan pada memahami kemanusiaan memberikan dasar bagi sikap humanistik yang ingin dibangun oleh Gus Dur. Pendidi kan humanistik dalam konsep Gus Dur adalah diskusi tentang nilainilai kemanusiaan yang disuarakan oleh Gus Dur yang mencakup kemanusiaan universal, hak asasi manusia dan keadilan. Oleh karena itu, makalah ini bermaksud membahas pendidikan humanistik dalam perspektif Gus Dur.